The real estate investment handbook - Haight, G. Timothy (Frank J. Fabozzi series., 2005)
A careful examination of the intricacies of real estate investing The Real Estate Investment Handbook provides readers with the necessary tools used by financial professionals to properly evaluate the opportunities in today's growing real estate market.